Optimal synthesis of ethylene production process - Khor, C.S. (Italian Association of Chemical Engineering - AIDIC, 2014)
This work addresses the energetic and economic optimization for the synthesis of distillation-based ethylene production. We employ a model-based optimization approach to determine the optimal sequencing of processes for olefins separation that involves handling a multicomponent mixture. The optimization model is formulated based on a superstructure that embeds many possible and feasible structural alternatives for processing a number of hydrocarbon components constituting gaseous ethane or liquid naphtha. We adopt linear mass balance reactor models for conversion of materials into desirable products and simple sharp distillation column models based on split fractions for product recovery from a multicomponent feed stream. The formulation leads to a mixed-integer linear program (MILP) with discrete 0-1 variables on task selection and continuous variables on input flowrate to each task. To aid convergence to the optimal system synthesis with minimum total annualized cost, the model incorporates heuristic-based logical constraints that represent design and structural specifications on engineering knowledge, design experience, and rules of thumb. The model is implemented on case studies drawn from actual operating petrochemical plants in Malaysia with reasonable computational results. Copyright Â© 2014, AIDIC Servizi S.r.l.